Coronavirus infection: An immunologists' perspective - De Sanctis, Juan Bautista; García, Alexis Hipólito; Moreno, Dolores; Hajduch, Marián (Scandinavian journal of immunology, 2021)
Coronavirus infections are frequent viral infections in several species. As soon as the severe acute respiratory syndrome (SARS) appeared in the early 2000s, most of the research focused on pulmonary disease. However, disorders in immune response and organ dysfunctions have been documented. Elderly individuals with comorbidities exhibit worse outcomes in all the coronavirus that cause SARS. Disease severity in SARS-CoV-2 infection is related to severe inflammation and tissue injury, and effective immune response against the virus is still under analysis. ACE2 receptor expression and polymorphism, age, gender and immune genetics are factors that also play an essential role in patients' clinical features and immune responses and have been partially discussed. The present report aims to review the physiopathology of SARS-CoV-2 infection and propose new research topics to understand the complex mechanisms of viral infection and viral clearance.
Keywords: complement; memory cells; Immunity, Innate; angiotensin-konvertující enzym 2; Humans; coronavirus; Host-Pathogen Interactions; Receptor, Angiotensin, Type 2; interakce hostitele a patogenu; cytokiny; Receptors, Virus; podskupiny lymfocytů; virové receptory; lidé; Biomarkers; syndrom uvolnění cytokinů; Angiotensin-Converting Enzyme 2; Virus Replication; Disease Susceptibility; náchylnost k nemoci; COVID-19; Energy Metabolism; innate immune response; Lymphocyte Subsets; biologické markery; energetický metabolismus; receptor angiotensinu typ 2; Cytokine Release Syndrome; Cytokines; replikace viru; SARS-CoV-2 infection; Inflammation Mediators; SARS-CoV-2; cytokine storm; immune response; mediátory zánětu; přirozená imunita